Dialectics of Transnational Mobility, Class, and Cultural Intermediary among Indonesian Migrant Worker-Students in South Korea - Madrah, Muna Yastuti; Suharko, Suharko; Sartika, Diana Dewi (JSW (Jurnal Sosiologi Walisongo), 2021)
Cosmopolitanism among migrant workers may present as the result of interpretations between transnational mobility, class, and cultural intermediary. Applying the ethnographic method this research was carried out during 2018-2019, which took Indonesian migrant worker-students aged 20-35 years in South Korea as informants. Travel and immigration, and higher education experiences have left Indonesian migrant workers at work in any places both in and out of campus areas. These practices show that the broader social, cultural, and individual agendas are one way of recognizing a new cosmopolitanism. There are two factors that influence the cosmopolitanism process of Indonesian migrant workers; first, the transnational migration process. Second, the process of cultural intermediation in universities. This study reveals significant differences in how Indonesian migrant workers respond to the possibilities and opportunities of transnational mobility, from developing the cultural acceptance skills needed in their life trajectories for building network relationships with other transnational actors. Higher education for migrant workers has introduced another form of work, namely cultural intermediation, which can be seen as a cosmopolitan process._________The original draft of this article has been presented on the International Conference on Language, Linguistics, and Literature (COLALITE) UNSOED, 2020.